Ruinous Modernity. On the Aesthetics, Critique, and Mediality of Decay - Dauss, Markus (Artium Quaestiones, 2025)
Ruins are a distinct architectural state, marked by decay and temporal exposure, challenging traditional monumentality. They have long fascinated through their ambivalence—oscillating between dereliction and beauty. Recently, ruins have regained theoretical attention, reflecting both material transformations (ruins of modernity) and shifting perceptions of architecture. The paper links contemporary ruin discourse with historical perspectives, showing how cultural frameworks shape their interpretation. Ruins prove to be a central starting point for exploring the significance of time in architectural perception, while also accounting for the transmedial factors involved. Since the 18th century, ruins have been valued increasingly aesthetically rather than merely lamented as remnants of loss. The term ruin lust captures this shift, exemplified by Denis Diderot’s reflections on decay as a poetic force. While classical ruins were dignified by history, modern ruins—especially abandoned industrial sites—lack this aura. Originally simply discarded as quickly consumed utility objects, they have since entered heritage discourse, though their status remains contested. This engagement is reflected in Urban Exploration (Urbex), which transforms decaying spaces into sites of discovery and visual documentation. However, Urbex is often criticized as ruin porn, a voyeuristic staging of decay that ignores social and historical complexity. This ethical dilemma underscores a broader issue: the ruinous state often involves not only physical structures but also the communities displaced by decline. Beyond their social impact, ruins evoke a profound sense of the uncanny. Unlike Gothic ruins, often associated with aristocratic decline, modern ruins unsettle through emptiness and infrastructural decay. Many modernist buildings appear ruinous from the outset, revealing the latent melancholy of functionalist design. Postmodernism plays with artificial ruins and ironic nostalgia, further complicating the ruin discourse by blurring the line between authenticity and staged decay. Today, ruination extends beyond architecture to entire ecosystems. Industrial and nuclear wastelands serve as monuments to environmental collapse. Unlike classical ruins, which often harmonized with their surroundings, contemporary ruins resist integration into nature, exposing planetary instability. In this sense, ruination reflects not just the past but an uncertain future. Ruins have always been tied to media, particularly writing and photography, which preserve traces of history. Photography mirrors ruins in its fragmentary nature, capturing both historical monuments and modernity’s accelerating decay. The paper shows that ruins are not just remnants but dynamic spaces of interpretation, where destruction, memory, and aesthetics intersect.